Solve for y 6(y+3)-2y=2(2y+1)

Math
6(y+3)-2y=2(2y+1)
Simplify 6(y+3)-2y.
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
6y+6⋅3-2y=2(2y+1)
Multiply 6 by 3.
6y+18-2y=2(2y+1)
6y+18-2y=2(2y+1)
Subtract 2y from 6y.
4y+18=2(2y+1)
4y+18=2(2y+1)
Simplify 2(2y+1).
Tap for more steps…
Apply the distributive property.
4y+18=2(2y)+2⋅1
Multiply.
Tap for more steps…
Multiply 2 by 2.
4y+18=4y+2⋅1
Multiply 2 by 1.
4y+18=4y+2
4y+18=4y+2
4y+18=4y+2
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 4y from both sides of the equation.
4y+18-4y=2
Combine the opposite terms in 4y+18-4y.
Tap for more steps…
Subtract 4y from 4y.
0+18=2
Add 0 and 18.
18=2
18=2
18=2
Since 18≠2, there are no solutions.
No solution
Solve for y 6(y+3)-2y=2(2y+1)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top